An introduction to genetic association analysis - Barrett, Jenny (Henry Stewart Talks, 2016)
What is genetic association, Testing for genetic association, Quantitative trait analysis, Covariates, Family-based tests, Multi-SNP models
Reviewed at 2025/03/31